Nickel and cobalt release from beauty tools: A field study in the German cosmetics trade - Symanzik, Cara; Uter, Wolfgang; Becker, Selina Marie; Skudlik, Christoph; John, Swen M. (Contact Dermatitis, 2022)
Background: Relevant nickel and cobalt release from hairdressing tools has recently been evidenced. Comparable data are not available for tools used in beauty salons. Objectives: Screening of beauty tools for nickel and cobalt release. Methods/Materials: Three hundred eight beauty tools were tested in seven beauty salons located in two North-German states. A nickel spot test and a cobalt spot test were used to test the tools for nickel release and cobalt release, respectively. Results: One hundred forty-three of 308 beauty tools overall (46.4%; 95% confidence interval [CI]: 40.8%-52.2%) released nickel and 18 of 308 beauty tools overall (5.8%; 95%CI: 3.5%-9.1%) released cobalt. Nickel release was found in 22 of 99 metal tools (22.2%; 95%CI: 14.5%-31.7%) and 121 of 209 tools with metallic parts (57.9%; 95%CI: 50.9%-64.7%); cobalt release was detected in 3 of 99 metal tools (3.0%; 95%CI: 0.63%-8.6%) and 15 of 209 tools with metallic parts (7.2%; 95%CI: 4.1%-11.6%). Conclusions: Nickel and cobalt are emitted at allergologically relevant levels by a wide range of beauty tools (i.e., metal tools and tools with metallic parts) utilized in the German cosmetics trade. Beauty tools should thus be considered occupational sources of nickel and cobalt exposure.
CRIS-Team Scopus Importer:2022-04-15
Keywords: aesthetician; beautician; cobalt; cosmetician; Germany; nickel; spot test; tool